2005
DOI: 10.1093/ptj/85.12.1329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bracing and Other Conservative Interventions in the Treatment of Idiopathic Scoliosis in Adolescents: A Systematic Review of Clinical Trials

Abstract: Background and Purpose. Many conservative treatments are available for adolescents with idiopathic scoliosis, but the evidence for their accepted use is still unclear. The purpose of this study was to evaluate the effectiveness of braces and other conservative treatments of idiopathic scoliosis in adolescents by systematically reviewing the literature. Methods. The literature was searched in the PubMed, CINAHL, Cochrane, and PEDro databases. Studies were selected if the design was a randomized clinical trial o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(74 citation statements)
references
References 30 publications
2
71
0
1
Order By: Relevance
“…Treatment options for the prevention of AIS progression include exercises, bracing, and surgery [1,[19][20][21][22][23][24][25][26][27][28][29]. Bracing can be defined as the application of external corrective forces to the trunk.…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…Treatment options for the prevention of AIS progression include exercises, bracing, and surgery [1,[19][20][21][22][23][24][25][26][27][28][29]. Bracing can be defined as the application of external corrective forces to the trunk.…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…For moderate deformities, bracing is the most common treatment. However, its efficiency in preventing the progression of scoliotic deformities is still controversial [14,17,19,20,29]. Many questions remain about what could be the best brace design.…”
Section: Introductionmentioning
confidence: 99%
“…Early treatment by bracing is thought to prevent further progression of the curvature and thereby to prevent the need for surgery [6,7]. The effectiveness of bracing, however, has not been sufficiently established due to a lack of randomized controlled trials (RCT) [15,24]. The studies on bracing that have been done were mostly retrospective studies, or studies without a control group.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that bracing was effective. However, this study was non-randomized, non-blinded and with baseline differences between the groups [15,24]. Several authors have stated that a RCT, in which the control group (initially) is not offered brace treatment, should be conducted [8,9,14].…”
Section: Introductionmentioning
confidence: 99%